The readiness of cloud computing: a case study in Politeknik Sultan Salahuddin Abdul Aziz Shah / Farah Hanim Mohd Fauzi - Mohd Fauzi, Farah Hanim (2014)
Cloud computing is a new technology that provides flexible and massive online computing power. There are many cloud computing systems nowadays, for example Google, Windows, IBM and Amazon. Nowadays, the demands for computing resources were increase. The companies would found that, by using outside computing resources was more economical than build a new computing capacity internally. Mostly, cloud computing allows a company to expand their network and server infrastructure. Some of cloud computing services will add more network and server capacity to company web sites as demand for services of the Web site increase. The readiness to adopt new technology requires a deep understanding of the technology and the adoption factors that drive the organization to make decision to adopt new*technology. This study aims to investigate the readiness towards Cloud Computing in Politeknik Sultan Salahuddin Abdul Aziz Shah. The significance for this research is this study will contribute for some ideas and understanding about cloud computing implementation in the organization especially for the researchers who are doing a research on the effectiveness of cloud computing application. This study will be conducted at Unit Teknologi Maklumat (UTM) and Jabatan Matematik, Sains and Komputer, Politeknik Sultan Salahuddin Abdul Aziz Shah and focus on the readiness towards cloud computing application. Conceptual Model for Cloud Computing Adoption is a model used to identify the factors that drive an organization to get ready in implementing Cloud Computing services. The level of readiness to adopt Cloud Computing will be investigated by using Cloud Computing Maturity Model, which consists of maturity assessment and adoption assessment. Responses from IT experts from Politeknik Sultan Salahuddin Abdul Aziz Shah were analyzed and the rating scores from the assessments will indicate the level of readiness towards cloud computing in PSA. The expected results for this study will help the organization to measure the level of readiness towards cloud computing application. Besides, the study also helps to measure how the organization accepted, embrace and applied cloud computing within their organization. The recommendation for this study is the study should be explored with large size of respondents includes students. Besides, other recommendation is the top managements should be chosen as one of the respondents to get more accurate evaluations and results.